Evaluasi Program Pembinaan Prestasi Olahraga Renang Di PRSI Kabupaten Sarolangun - *Jannatul Khairoh; Argantos Argantos; Arsil Arsil; Gusril Nasir (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
The problem in this study is the decline in swimming sports achievement in Sarolangun Regency, as seen from the acquisition of medals at the PorProv Jambi event for the last three periods. CIPP model. The purpose of this study is of course to evaluate the swimming sports achievement coaching program at PRSI Sarolangun Regency.This type of research is qualitative, the research method used is program evaluation with the CIPP model. For informants, namely the management, trainers, and the chairman of BimPres. Collecting data through observation, interviews, documentation. The results of the evaluation show that, (1)the context aspect, the coaching program carried out aims to produce high-achieving athletes, both at the regional, provincial, national and even international levels. This is already relevant to the Vision and Mission of PRSI. (2)input aspect, there is a written management structure, already has a coach who is certified or already has a license, lots of good potential to become a swimming athlete, it's just that interest is lacking, facilities and infrastructure are already available but need maintenance and renewal, no there is funding transparency, and there are no written planning documents and training programs (daily, weekly, monthly, and yearly as well as training manuals). (3)the process aspect, there are no small clubs for the athlete regeneration process only taking from O2SN activities, there is no written preparation of the coach in the implementation of training weight training which is given not based on coaching knowledge only refers to the coach's experience who was formerly a swimming athlete, and (4)Product aspects, achievements at the Jambi PorProv event which he attended in 2012, 2015 and 2018.